Divorcio y su incidencia en la formación integral de los adolescentes, estudio de casos en la ciudadela 10 de Agosto de la ciudad de Santa Rosa, período 2012-2013. - Rogel Ramírez, Jéssica del Rocío (2013)
To carry out research use as a working tool to the interview which was conducted both parents and their teenage children, with the aim of knowing the problems and the effect caused by divorce each household member.